PARADIPLOMASI KOTA BUKITTINGGI DENGAN MALAYSIA DALAM MENINGKATKAN KUNJUNGAN WISATA - Muhammad Fhadly, Poppy Irawan, Rika Isnarti (Fakultas Ilmu Sosial Ilmu Politik Pr, 2018)
This research aims to explain parad[1]iplomacy of Bukittinggi’s government to Malaysia in order to improve number of Malaysian tourism to Bukittingi and the impact of the paradiplomacy. Malaysian tourism is the highest number of tourism visting Bukitting. This situation benefits bukittingi especially in the economy sector that can empower small and medium entreprises. However, the government needs to do actions to attract more tourists to Bukittingi to enhavce economic benefit. In International Relations, Substate doing international affairs can be done through paradiplomacy. The type of this research is descriptive analysis using two types of data, namely documentation and interviews. The results of the research showed that the paradiplomacy of Bukittinggi to several regions in Malaysia is carried out through an approach that focuses on the education and culture sectors. Paradiplomacy activities between Bukittinggi and several regions in Malaysia provide benefits to Bukittinggi in order to expand the MSME market and have impact on optimizing the production of kerancang embroidery.